Hessian Fly (Mayetiola destructor [Say]) Resistance Identified on Chromosome 1AS in the Spring Wheat (Triticum aestivum L.) Cultivar 'Louise'. Issue 3 (1st May 2014) - Carter, A. H.; Cambron, S. E.; Ohm, H. W.; Bosque‐Pérez, N. A.; Kidwell, K. K.
ABSTRACT: The Hessian fly ( Mayetiola destructor [Say]) is a major yield‐limiting pest in wheat ( Triticum aestivum L.) production systems. Resistant varieties provide the most effective control method. The objectives of this study were to identify the chromosomal location of and molecular markers associated with the Hessian fly resistance from the spring wheat cultivar 'Louise'. One hundred eighty‐eight F5:6 recombinant inbred lines (RILs) from a Louise (resistant) × 'Penawawa' (susceptible) cross were evaluated for resistance to Hessian fly biotype C and a mixed population originating from field collections in the Pacific Northwest (PNW). Eight to 15 plants per RIL were scored for resistance at Purdue University and the University of Idaho. Data were converted to percentages of susceptible plants within each RIL. Louise and Penawawa had averaged susceptibility values of 15 and 100%, respectively. The RIL population ranged from 0 to 100% susceptible. A genetic linkage map consisting of 320 simple sequence repeat and 8530 single nucleotide polymorphism DNA markers was used for quantitative trait locus (QTL) analysis. One QTL, identified as QHf.wak‐1A, was significantly associated with Hessian fly resistance at an average LOD of 26.2 and accounted for 77% of the phenotypic variation. QHf.wak‐1A was localized to a 4.6‐cM region on chromosome 1AS, flanked by markers Xiwb70039 and Xcfd15 . Marker, biotype screening, and allelism results indicate that this QTL is different from H9, H11, H5, and H3, but linked to H3 and H5 . These data continue to clarify the relationship between Hessian fly genes on chromosome 1AS and would facilitate breeding efforts.